Factors influencing the survival of implant-supported ceramic-ceramic prostheses: A randomized, controlled clinical trial. Issue 3 (May 2020) - Esquivel-Upshaw, J.F.; Mecholsky, J.J.; Clark, A.E.; Jenkins, R.; Hsu, S.M.; Neal, D.; Ren, F.
Highlights: A randomized clinical trial was performed on the largest cohort of implant-supported fixed dental prostheses. Design parameters which influenced in vitro failure in restorations were tested clinically. Design parameters included type of material, veneer thickness, radius of curvature of gingival embrasure and connector height. Analysis of fracture origins and stresses at fracture determined that almost all fractures originated from the occlusal surface. Clinically, none of the design parameters demonstrated significance but veneer thickness could have an influence if sample size was larger. Abstract: Objective: The goals of this research are: (1) to determine the clinical survival of ceramic-ceramic 3-unit implant supported fixed dental prostheses (FDPs) compared with control metal-ceramic and; (2) to analyze the effects of design parameters such as connector height, radius of curvature of gingival embrasure, and occlusal veneer thickness. Materials and Methods: This randomized, controlled clinical trial enrolled 96 participants with 129 3-unit implant-supported FDPs. Participants were randomized to receive different design combinations to include FDP material, thickness of occlusal veneer ceramic, radius of curvature of gingival embrasure and connector height. Participants were recalled for 6 months, 1 year and yearly thereafter for the next 5 years. FDPs were examined for evidence of fracture and radiographs were made to assess viability of implants. Fractographic analyses and Kaplan Meier survival analysis was used to analyze the data. Results: 27 FDPs, representing 21%, exhibited chipping fractures of the veneer during the 5-year observation period. There was no statistically significant effect of type of material, veneer thickness, radius of curvature of gingival embrasure and connector height on occurrence of fracture. Fractographic and occlusal analyses reveal that fractures originated from the occlusal surface and that occlusion was the most important factor in determining survival. Stresses calculated at failure demonstrated lower values compared with in vitro data. Conclusion: Implant-supported ceramic-ceramic prosthesis is a viable alternative to metal-ceramic. Survival analysis for both materials were comparable and design parameters employed in this study did not affect survival as long as zirconia was used as the core material.